PROSPEK PENGEMBANGAN INDUSTRI KERAJINAN ATAP DAUN RUMBIA DI DESA KEPAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Khairiyati Hasan; Jahrizal '; Eka Armas Pailis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted in the Kepau Jaya of village Siak Hulu subdistrict Kampar district . The purpose of this study was to determine the development of leaf thatched roof cottage industries in the village Kepau Jaya of Siak Hulu subdistrict Kampar district. In this study sample using simple random sampling, with a total sample of 43 respondents. This study uses primary and secondary data. Technique data collecting qualitative data by the method of observation, questionnaire , and interviews. Data analysis method used is descriptive analysis. This study shows that, sago palm leaf roof cottage industries included in the home industries, handicrafts leaf thatched roof is a roof made of sago palm leaves that are woven by the women in Village Kepau Jaya. raw material in producing leaf roof is sago palm leaves, bamboo, and rattan. The process of producing sago palm leaf roofs are not wearing labor, using only family labor (Family Workers). Capital expended in producing sago palm leaf roofs around Rp 35.000 - Rp 40.000. Craftsmen could produce sago palm leaf roof of 200-250 pieces to order, the selling price of Rp 140.000 sago palm leaf roof - Rp 150.000/100, and Rp 1.400/lembar, the demand for leaf thatched roofs are still much in demand by enthusiasts, inhibiting factors in producing leaf roof thatch is damaged road infrastructure, season and health craftsmen.Keywords: leaf thatched roof cottage industries, small industries, potential raw material, inhibiting factors.